Prediction of Pearl Millet Yield Using Crop Water Balance Model for Different Agroclimatic Zones of Gujarat State - Sahu, D D; Sastry, P S.N; Dixit, S K; Pandya, H R (Annals of Arid Zone, 2016)
Water requirement satisfaction index (WRSI) -as worked out using a crop water balance (CWB) model in respect of pearl millet crop in various agroclimatic zones of Gujarat State. Different regression models were tried to find out a best fit model to predict and estimate pearl millet productivity at different stations. The best fit curves explained variation in pearl millet yield ranging from a maximum of 94% at Jamnagar to 57% at SK Nagar. A single equation could not predict yield at all the stations, may be because of significant type of climatic conditions prevailing at each place. Statistical attributes like coefficient of determination (R2 ) and correlation coefficient (r) between estimated and actual yield indicated that the concept of WRSI could be utilized to predict pearl millet yield in low and erratic rainfall stations of Gujarat state.